Antecedents of luxury brand hate: A quantitative study. (8th January 2021) - Bryson, Douglas; Atwal, Glyn; Hultén, Peter; Heine, Klaus
Abstract: This study analyses the relationships of the antecedents of "extreme negative affect" toward luxury brands. The results show that the first‐order predictors of luxury brand hate were negative stereotypes of people who use the luxury brand, consumer dissatisfaction with the brand, and negative word‐of‐mouth. The following three strategic approaches: (a) proactive, (b) neutral, and (c) reactive can be considered as a template to address the causes and implications of brand hate.